Anterolateral territory coronary artery bypass grafting strategies: a non-inferiority randomized clinical trial: the AMI-PONT trial. (20th February 2023) - Stevens, Louis-Mathieu; Chartrand-Lefebvre, Carl; Mansour, Samer; Béland, Vincent; Soulez, Gilles; Forcillo, Jessica; Basile, Fadi; Prieto, Ignacio; Noiseux, Nicolas
Abstract: OBJECTIVES: The main objective was to assess whether a composite coronary artery bypass grafting strategy including a saphenous vein graft bridge to distribute left internal mammary artery outflow provides non-inferior patency rates compared to conventional grafting surgery with separated left internal mammary artery to left anterior descending coronary graft and aorto-coronary saphenous vein grafts to other anterolateral targets. METHODS: All patients underwent isolated grafting surgery with cardiopulmonary bypass and received ≥2 grafts/patients on the anterolateral territory. The graft patency (i.e. non-occluded) was assessed using multislice spiral computed tomography at 1 year. RESULTS: From 2012 to 2021, 208 patients were randomized to a bridge ( n = 105) or conventional grafting strategy ( n = 103). Patient characteristics were comparable between groups. The anterolateral graft patency was non-inferior in the composite bridge compared to conventional grafting strategy at 1 year [risk difference 0.7% (90% confidence interval –4.8 to 6.2%)]. The graft patency to the left anterior descending coronary was no different between groups ( P = 0.175). Intraoperatively, the bridge group required shorter vein length for anterolateral targets ( P < 0.001) and exhibited greater Doppler flow in the mammary artery pedicle ( P = 0.004). The composite outcome of death, myocardial infarction or target vessel reintervention at 30 days was no different ( P = 0.164). CONCLUSIONS: Anterolateral graft patency of the composite bridge grafting strategy is non-inferior to the conventional grafting strategy at 1 year. This novel grafting strategy is safe, efficient, associated with several advantages including better mammary artery flow and shorter vein requirement, and could be a valuable alternative to conventional grafting strategies. Ten-year clinical follow-up is underway. Trial registration: ClinicalTrials.gov : NCT01585285. Abstract : Coronary artery bypass grafting (CABG) surgery is associated with improved survival and quality of life in patients with severe ischaemic heart disease, especially those with left main, triple vessel disease or stenosis of the proximal left anterior descending coronary artery (LAD) [1].